Isi, Misi, Dan Sifat Pendidikan Islam Dalam Perspektif Al-Quran - Say, Wulan; Salmiwati, Salmiwati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to find out the vision of Islamic education from the Al-Qur'an. This research is qualitative. The methodology and approach used is content analysis. This article concludes that the vision of Islamic education according to the Qur'an is to form a talented Muslim personality, both intellectual and personality (moral/moral) talent. In addition, for him to be competent in the life of Islamic education, he must also have a pragmatic goal, namely to equip skills that are relevant to thedemands of the times. With this talent, a person will be able to realize world civilization ('umran) and prosper it. This goal is in line with the function of human creation as caliph on earth. When every human being can become a caliph in the truest sense, he will be a blessing for the universe (rahmatan lil 'lamîn) as the role of the Prophet Muhammad as a prophet for all mankind.